2018
DOI: 10.4103/sni.sni_94_18
|View full text |Cite
|
Sign up to set email alerts
|

Physician leadership and hospital ranking: Expanding the role of neurosurgeons

Abstract: Background:Empirical studies that explore whether hospitals with physician leadership perform better than hospitals led by nonphysician managers are scarce. This study looks at the leaders currently being hired by hospitals in the Arab World and explores whether chief executive officers (CEOs) in hospitals ranked higher are typically physician leaders or nonphysician managers. Furthermore, we discuss whether physicians, especially neurosurgeons, are equipped to lead hospitals and healthcare institutions worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The poor status of biomedical research in the Arab world, in general, can be a major reason behind the low output in health communication 41–43. The lack of infrastructure and the continuous migration of researchers towards Western countries that offer better living and work opportunities exacerbate the problem 6 42. More importantly, political instability and military conflicts in many of the Arab states,44 like Syria, Yemen, Iraq, Palestine and Libya, are a major obstacle for the development of clinical research, in general, and health communication, in specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor status of biomedical research in the Arab world, in general, can be a major reason behind the low output in health communication 41–43. The lack of infrastructure and the continuous migration of researchers towards Western countries that offer better living and work opportunities exacerbate the problem 6 42. More importantly, political instability and military conflicts in many of the Arab states,44 like Syria, Yemen, Iraq, Palestine and Libya, are a major obstacle for the development of clinical research, in general, and health communication, in specific.…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, the health scene in the Arab world has become increasingly intricate. Although countries of the Arab world are pretty diverse, most of the 22 countries that comprise the Arab League and share the common language of Arabic are embroiled in conflict, instability, poverty and/or corruption 6. This takes its toll on the health sector, whereby the need to address public health problems like war injuries, refugee crises, pollution, and communicable and non-communicable diseases rises 7…”
Section: Introductionmentioning
confidence: 99%
“…The lack of academic freedom, poverty, political instability, and conflict are important contributors of low research output. [ 1 61 62 63 64 ] With the rapid rise in use and popularity of social media platforms, health communication, as a field, will become a major tool to address public and global health needs. [ 65 ] As such, more efforts ought to be exerted to promote a research culture that make use of the current rise of communication media to promote healthy lifestyles and habits in LICs.…”
Section: Discussionmentioning
confidence: 99%
“…62 This would save time and allow the physician to focus on optimizing patient treatment and bettering clinical outcomes. 63,64 In addition, recent studies have shown that the use of AI can help reduce the amount of contrast agents used in imaging, like gadolinium, while significantly improving the quality of MRI. 65 This would prevent contrast-related toxicity and accumulation in brain tissue.…”
Section: Discussionmentioning
confidence: 99%